Sport, Culture and Purchasing Power: Influences on Food Markets and Consumption - Leon Gomboş; Alexandra Gabriela Milon; Ramona Ancuţa Nuţ; Cristina Dragomir; Alexandru Andrei Gherman (Amfiteatru Economic)
This study aimed to investigate the influence of economic, cultural, and lifestyle factors on food consumption patterns in 31 European and associated countries between 2010 and 2020. A panel econometric model with random effects was used to analyse data from international sources, including GDP adjusted for purchasing power parity, cultural indices, and food consumption statistics. The findings revealed that increased sports participation and purchasing power significantly increased vegetable, fruit, and fish consumption, while cultural values such as individualism and long-term orientation shaped dietary preferences. Unlike previous research that focused on individual-level factors, this study integrated macroeconomic determinants to provide a comprehensive analysis of national food consumption trends. Furthermore, critical shifts in the food market were identified, including the increasing demand for healthy and sustainable products, highlighting the challenges faced by food chain actors in adapting to these changes. The results provide a valuable framework for policy makers and business strategies, highlighting the need for resilience, innovation, and market adaptation to align with evolving consumer preferences.